The influence of Compression Ratio to Performance of Four Stroke Engine Use of Arak Bali as a Fuel - Krishna Muku, I Dewa Made; Sukadana, I Gusti Ketut (Jurnal Energi Dan Manufaktur; Vol 3, No.1 April 2009)
Arak bali is alternative fuel as ethanol. Ethanol has octane number 108. Octane number which was higher can over come adetonation, and can work at higher compression ratio. This experiment has done to now how the effect of compression ratiovariation to the performance four strokes engine by arak bali fuel. This research was done by changing the compressionratio that is 8,8 : 1, 8,9 : 1, 9 : 1 and 9,3 : 1. The change was done by reducing combustion chamber by scrap the cylinderhead. The result, for the used arak bali fuel to the vehicle is, if engine compression ratio to increase can be influence ofengine performance to be increase and engine fuel consumption to be decrease. For premium is, if engine compression ratioto increase to influence of engine performance to be decrease and engine fuel consumption to be increase.
Keywords: Compression ratio, Arak bali, Engine performance, Fuel consumption